Mensuração de resultados em comunicação : conceitos e práticas em ambientes de inovação - Suminski, Luciano Nunes (2017)
Working with measurement of results in communication consists of monitoring the development of research strategies and management of business communication, transforming the approach to the subject into a contemporary interest whilst being bonded to a need of contemplating technological advances, which are multiplying fast. More than relevant, the measurement of results in communication is a real and promising possibility for the partial understanding of the influences of these multiple changes, including in the Organizational Culture. This study treats the subject by approaching concepts and practices geared up for innovation and creativity, which are increasingly part of the organizational environments, making the management of relationships a challenge for media professionals, who need to reconcile new concepts of production and services with the traditional search for immediate results. In its development, the study establishes relationships between theory and practice of measurement of results in communication in environments of innovation, contemplating the execution of exploratory research with a Startup. This dissertation intends to contribute to a better understanding of the phenomena of business communication results, investigating the Startups as companies that are open to learning and to uncertainties, and that may represent a laboratory of experimentation on new organizational concepts and practices with regards to communication.